The Impact of Media Priming on Public Awareness of Development Issues in Adamawa - Yadima, Gaius Jeff (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study examines the impact of media priming on public awareness of development issues in Adamawa. Using the priming theory as a framework, the research explores how media exposure influences public perception, prioritisation, and engagement with development topics such as health, environment, and social change. The study analyzes media content and audience responses to determine the extent to which priming shapes awareness and attitudes. The study was anchored on priming theory. Findings reveals that media priming shapes political behavior, influences public support, media messages affect environmental communication, racial priming reinforces stereotypes and further recommends that media literacy education, balanced content, ethical media practices and public awareness to abreast the audience about media priming should be encouraged to help them make informed decisions.